The cognitive alignment of mathematics teachers’ assessments and its curriculum - Firdha Mahrifatul Zana; Cholis Sa'dijah; Susiswo Susiswo (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to explore how the cognitive level alignment between the teachers’ assessments and Mathematics curriculum in Indonesia related to students’ higher order thinking skills (HOTS) development. The study adopted a descriptive exploratory design with a qualitative approach. The participants of this study were 15 high school mathematics teachers from Malang City and the Nganjuk district. Data were collected from the results of the assessments and indicators of the mathematics curriculum used by teachers. The data collected were analyzed using Anderson & Krathwohl’s Taxonomy to determine the alignment of the cognitive level from assessments and curriculum. In the semi-structured interview session, we recorded teachers’ responses who were able to construct HOTS-based assessments. Our findings showed: i) mathematics indicators primarily targeted students’ thinking skills at the low cognitive level, namely applying; ii) teachers’ assessments were more dominant at the low cognitive level, and there was no assessment at create level; and iii) the alignment of the cognitive level was relatively low for the HOTS category. The study findings can be used to improve curriculum and assessment in education. They can also be used as reflections for Mathematics teachers on the importance of aligning the cognitive level, especially that develop students’ HOTS.